O Ensino de física com uso de aparelhos de imagem diagnóstica: Um estudo comparativo - Rodrigues Jr, Francisco Carlos Ribeiro (2017)
The present era has been marked by an aggressive process of social, economic, political and social changes that has implied in new forms of subjectivation and understanding of the world. The new technologies of information and communication supported by the Internet have also implicated in ever more complex and mediated forms of learning. Such changes have had repercussions in the classroom through the teacher's search for new ways of teaching. The use of material resources that potentiate teaching and learning has been common in this quest for improved teaching. Thus, this research had as general objective to analyze the teaching of physics from the use of the diagnostic imaging machine. It had specific objectives: To establish the relations between the teaching of physics and the machine; Historicize technical and technological education; Report the historical processes of physics teaching; Describe how the development of radiology teaching occurred. The research worked as two groups, namely: research group that had access to the machine in the production of the Radiological Physics discipline and the control group that did not have this same access, constituting a merely expositive class. As a research technique, a Likert Scale questionnaire was used to evaluate the use of the machine and its pedagogical potential. Then, an open questionnaire was applied with the objective of verifying how the students evaluate the use of the diagnostic imaging machine, aiding in the learning of physics. A questionnaire was also applied to verify the learning of the research and control groups. Comparative tabulations and analyzes were performed using the statistical software SPSS for Windows (Statistic Package for Social Science version 20.0) using graphs, tables and tables that express the data obtained. The target audience were students of a technical course in radiology from a private university in Fortaleza. Regarding the analysis of the results of the research was used a quantitative qualitative approach. The research concluded that the knowledge produced by the two groups was not significant to the point that the use of the machine influence significantly in the students' learning.